Penilaian Kompetensi Sikap dalam Pembelajaran Sejarah: Sebuah Telaah Literatur - Maryam Maryam; Idi Warsah (UIN Fatmawati Sukarno Bengkulu, 2022)
Affective domain is one of essensial competencies in educational world, especially history learning. Therefore, effective competence must be included in the learning objectives, strategies, and also measurement. However, due to lack of knowledge, skills, and awareness, affective competence often do not receive serious ettention from teachers. The porpuses of this research is to conducted literature review about measurement of affective domain in history learning. Three focus in this study are: 1) hakekat affective competencies; 2) affective competencies in history learning; dan 3) measurement instrument of affective competencies in history learning.This research was conducted with library research. The research steps undertaken are: 1) preparing tools and equipment; 2) compiling a working bibliography; 3) arranging research time; 4) reading and making research notes, and 5) concluding and analyzing the results of the research. The results of the research showed that: 1)afecctive competence is one of three main competence in education, especially history learning. Some thing that are included in affective competence are attitutes, interests, values and morals; 2) affective competence is essesial domain in history learning. In history learning, affective competence are focus to some attitude and values such as nationalism and historical values (tolerance, social care, loving peace, enveromental care, fairness, responsibilities, and others; 3) measurement of affective competence in history learning can be done through some strategies, but the most cummonty used attitude skale.